A saúde bucal de idosos pela perspectiva interprofissional - Freitas, Paula Rodrigues Barbosa de (Universidade Federal do Tocantins, 2024)
Population aging requires public policies that guarantee quality of life for the elderly through prevention, health promotion and comprehensive health care from a perspective of interprofessional collaborative practice in the work processes of Primary Care in the Brazilian Unified Health System (SUS). Edentulism, the total loss of natural teeth, has significant consequences on the general health and quality of life of completely toothless patients, justifying the involvement of all members of the Family Health Strategy (Estratégia Saúde da Família - ESF) and the Multiprofessional Team (Equipe Multiprofissional - eMulti) in geriatric care. This article aims to analyze how oral health care for fully edentulous elderly individuals is promoted by professionals working in Primary Health Care, with a focus on interprofessional work and the perspective of the elderly themselves. This is a qualitative study conducted from May to June 2024 through semi-structured interviews and focus groups with elderly individuals and professionals from a Family Health Unit (USF) in Palmas. Among the conclusions, interprofessionality is highlighted as a practice that does not reach the elderly and is not implemented, according to the professionals themselves, due to weaknesses in their training. This research outcome led to the development of a technical-technological product (PTT): the “Quick Guide to the Interprofessional Management of Edentulous Elderly for Primary Health Care Professionals without Dental Training.” This PTT is a tool to guide different professional categories in individual and/or collective clinical situations that require a collaborative and interprofessional approach with dental professionals, aiming to improve the overall health of edentulous patients.